Faktor-faktor yang mempengaruhi kecenderungan penerimaan opini audit Going Concern pada Perusahaan Manukafaktur yang terhadap di Bursa Efek Indonesia (BEI) - Irfan Irwandi (AKT 13 UMY 123, 2013)
This study aims to investigate the influence of Audit Quality, Financial Condition, Company Growth, Audit Opinion Previously, Company Size, and the DER to Going Concern Audit Opinion on manufacturing companies on the Stock Exchange. The population in this study are all companies listed on the Indonesia Stock Exchange in the period 2007-2011. Based on sampling techniques with purposive sampling method, the sample used by 25 manufacturing companies. These results indicate that only Financial Condition, Growth Company, Previous Audit Opinion and DER factors that influence acceptance of Going Concern Audit Opinion on manufacturing companies on the Stock Exchange. While the Audit Quality and Firm Size does not affect acceptance Going Concern Audit Opinion.